Determinan Organizational Citizenship Behaviour oleh Iklim Organisasi dan Gaya Kepemimpinan Transformasional - Leonora Ferdinandus; Cynthia Imelda Tjokro (Journal of Business Application, 2023)
This study aims to examine and analyze the magnitude of the impact of organizational climate and transformational leadership style on Organizational Citizenship Behaviour of PLP and laboratory technicians of Politeknik Negeri Ambon. The data collection for this survey used a questionnaire instrument with a total sample of 41 employees obtained using a census sample technique. The test results using multiple linear regression analysis techniques show that; organizational climate and transformational leadership have proven to have a positive and significant effect on Organizational Citizenship Behaviour of PLP and laboratory technicians. This means that encouragement to increase transformational leadership and working conditions will increase the Organizational Citizenship Behaviour of PLP and laboratory technicians of Politeknik Negeri Ambon.